Occurrence of Dioctophyme renale larvae (Goeze, 1782) (Nematoda: Enoplida) in a new host from southern Brazil - Mascarenhas,Carolina Silveira (2018)
Abstract Dioctophymatosis is caused by the giant kidney worm Dioctophyme renale which occurs in dogs, cats, and wild mammals. In Brazil, the disease has been diagnosed in dogs from several states around the country. In the present study, the occurrence of D. renale larvae in snakes from southern of Brazil is reported. Three specimens of Philodryas patagoniensis (Serpentes: Dipsadidae) (common names in Brazil: “parelheira”, “papa-pinto”) roadkill in the county of Capão do Leão, State of Rio Grande do Sul, southern Brazil, were necropsied. Two third-stage larvae of D. renale were found in the coelomic cavity of P. patagoniensis. This study reveals a new host for D. renale larvae in the southern region of the State of Rio Grande do Sul, Brazil. This particular geographic area of the country has stood out as several cases of D. renale infection have been reported in a number of vertebrates from this region including domestic dogs and cats and wild animals such as carnivores, fish, and freshwater turtles.